Previsibilidade em revoada de formigas-cortadeiras Atta sexdens rubropilosa Forel, 1908 (Hymenoptera, Formicidae) por meio de modelagem computacional - Tallarico, Luís Carlos (Universidade Federal de São Carlos, 2018)
The mating process of the leaf-cutting ants, genus Atta, represents a relevant event to be studied due to its biological interest. The mating coincides with the onset of the rainy season and the hottest period of the year, when, under very specific climatic conditions, winged males and females leave the adult colony for copulation, which occurs during flight, including between individuals from different colonies, aiming to increase the genetic variability of the population. The females then become the queens of new colonies that will be founded. The prediction of the mating period is important because it is fundamental information for monitoring the pest and for the planning of the application of methods for its control that enable: the reduction of the quantities and costs of the used inputs, the increase of the efficiency control agents and the reducing of the damage they can cause to the environment. It also facilitates the process of collecting these insects for use in experiments. The climatic conditions are an important factor for the definition of the period of the flock, however, there are few studies for the subject and there is no method or tool that uses mathematical modeling to predict its occurrence. The objective of this work was to estimate the mating period of leaf-cutting ant Atta sexdens rubropilosa occurs, based on climatic information and meteorological forecasts, through the construction of a computational model that involves data analysis and uses specific scoring functions, in an optimization process, that had its calibration based on the set of climatic data of a period and in the record of the respective dates in which the mating was observed. The optimization model was sufficiently sensitive and able to determine a maximum point, in terms of scoring, on the date on which the mating occurred.
Keywords: Saúva; Voo nupcial; Acasalamento; Modelo; Otimização; Leaf-cutter ants; Nuptial flight; Mating; Model; Optimization; CIENCIAS AGRARIAS; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::MATEMATICA DA COMPUTACAO::MODELOS ANALITICOS E DE SIMULACAO